The nexus between direct air capture technology and CO2 emissions in the transport sector - Unal, Emre; Keeley, Alexander Ryota; Kose, Nezir; Chapman, Andrew; Managi, Shunsuke (Elsevier Sci Ltd, 2024)
Deploying negative emission technologies has become crucial for limiting the global temperature rise to approximately 1.5 degrees C above preindustrial levels. DAC technologies are being explored as one of the prospective options. These technologies have been thoroughly investigated as a potential project to capture CO2 emissions and provide purified air, natural gas, or fuel oil. An applied approach, on the other hand, was not taken into consideration while evaluating the influence that this technology has on emissions. For this reason, British Columbia provides a substantial chance to examine emissions that were produced after the DAC actions were put into place in 2015. In this study, the difference-in-differences methodology is employed for the very first time to compare the emissions that are produced by the transport sectors in British Columbia with those emitted by other provinces in Canada. The role that GDP and population play in the release of emissions is also taken into consideration in this paper. Based on the research results, it can be observed that the implementation of DAC initiatives has yielded notable effects. Evidence shows that the DAC effort has led to an average reduction of 0.08 in logarithmic CO2 emissions in the transport sector. By accounting for GDP and population, the empirical results indicate that DAC technology reduced CO2 emissions in British Columbia compared to provinces without DAC facilities. DAC initiatives are expected to become increasingly prevalent between the mid-2030s and 2040s. Overall policy implications suggest that there is a need for DAC technologies to collaborate with alternative mitigation technologies, or alternative technologies should collaborate with DAC technologies that are more efficient to achieve the targeted goals in a short time.
Keywords: CO2 emissions; Difference-in-differences; Direct air capture; Transport sector